2017
DOI: 10.1007/s00198-017-3955-x
|View full text |Cite
|
Sign up to set email alerts
|

The associations between serum 25-hydroxyvitamin D level and the risk of total fracture and hip fracture

Abstract: Our study suggests that low serum 25(OH) vitamin D level is associated with increased risks of total and hip fractures. In the analyzed studies, the per SD decrease in serum 25(OH) vitamin D level was associated with the hip fracture risk but not with the total fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 58 publications
0
31
2
1
Order By: Relevance
“…Feng et al . reported that 25OHD was obviously associated with hip fractures in the elderly patients. For each reduction in standard deviation, major osteoporotic fractures increased by 40%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Feng et al . reported that 25OHD was obviously associated with hip fractures in the elderly patients. For each reduction in standard deviation, major osteoporotic fractures increased by 40%.…”
Section: Discussionmentioning
confidence: 94%
“…Annweiler and Beauchet found that the number of elderly patients who experienced falls and tumbles with a serum 25OHD below 20 ng/mL significantly increased the risk of fracture 19 . Feng et al reported that 25OHD was obviously associated with hip fractures in the elderly patients 20 . For each reduction in standard deviation, major osteoporotic fractures increased by 40%.…”
Section: Relationship Between Serum 25ohd Level and Brittlementioning
confidence: 99%
“…Hepatic encephalopathy is also associated with an increased risk of fall, which will increase the fracture risk. In addition, the limited ability to make 25‐hydroxy (OH) D in cirrhotic patients may increase fracture risks …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the limited ability to make 25-hydroxy (OH) D in cirrhotic patients may increase fracture risks. 23,24 This study has several limitations which should be noted.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 94%
“…However, Ginsberg et al [11] showed that there is no association between serum 25(OH)D and hip fractures, and that by Barbour et al [12] showed that serum 25(OH)D is unrelated with the occurrence of any non-spine fractures. In a 2017 metaanalysis on the relationship between serum 25(OH)D and the risk of total fractures, it was found that serum 25(OH)D is inversely proportionate to the incidence of total fractures [13].…”
Section: Introductionmentioning
confidence: 99%